PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM TRANSAKSI KONTRAK DAN BISNIS ELEKTRONIK - Armaswari, Luh Gede Putri Kanaya; Citra, Made Emy Andayani (Jurnal Hukum Mahasiswa, 2024)
Trade through high technology such as E-commerce has fundamentally changed traditional trading systems and conventional business paradigms in shaping interactions between producers and consumers in the digital world. The purpose of this research is to understand efforts to protect customers from potential losses in these transactions. This research method uses a normative approach by analyzing literature and secondary data to discuss consumer legal protection in the context of E-commerce. Law Number 19 of 2016 concerning Electronic Information and Transactions (UU ITE) is seen as one solution to provide protection to consumers.